2016
DOI: 10.1136/annrheumdis-2016-209467
|View full text |Cite
|
Sign up to set email alerts
|

Treat-to-target (T2T) recommendations for gout

Abstract: ObjectivesThe treat-to-target (T2T) concept has been applied successfully in several inflammatory rheumatic diseases. Gout is a chronic disease with a high burden of pain and inflammation. Because the pathogenesis of gout is strongly related to serum urate levels, gout may be an ideal disease in which to apply a T2T approach. Our aim was to develop international T2T recommendations for patients with gout.MethodsA committee of experts with experience in gout agreed upon potential targets and outcomes, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0
19

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 52 publications
(32 reference statements)
0
104
0
19
Order By: Relevance
“…G-CAN, like the ACP and rheumatology society panels, recognized that no long-term (that is, more than 12 months' duration) RCTs have specifically examined the treat-to-target approach to gout management. Moreover, the G-CAN expert panel, and a largely separate panel of rheumatologists 45 , agree with the ACP panel that evidence is still lacking for reduction in frequency of acute gout flares by oral ULT measures during the randomized, controlled phase of clinical trials. However, G-CAN strongly supports the treat-to-target The G-CAN expert panel unanimously agreed that patients should be given full information as laid out in this recommendation, but expressed concern that this recommendation lacks any clear advice concerning ULT and anti-inflammatory flare prophylaxis, and lacks sufficient specificity to provide practical guidance to clinicians…”
Section: Interpreting Limits Of Past Ult Trialsmentioning
confidence: 85%
See 1 more Smart Citation
“…G-CAN, like the ACP and rheumatology society panels, recognized that no long-term (that is, more than 12 months' duration) RCTs have specifically examined the treat-to-target approach to gout management. Moreover, the G-CAN expert panel, and a largely separate panel of rheumatologists 45 , agree with the ACP panel that evidence is still lacking for reduction in frequency of acute gout flares by oral ULT measures during the randomized, controlled phase of clinical trials. However, G-CAN strongly supports the treat-to-target The G-CAN expert panel unanimously agreed that patients should be given full information as laid out in this recommendation, but expressed concern that this recommendation lacks any clear advice concerning ULT and anti-inflammatory flare prophylaxis, and lacks sufficient specificity to provide practical guidance to clinicians…”
Section: Interpreting Limits Of Past Ult Trialsmentioning
confidence: 85%
“…ULT strategy, as the various rheumatology groups have consistently done, on the basis of the breadth of available evidence, including long-term, openlabel extensions of oral ULT RCTs, prospective observational studies, and the trials of intensive ULT with pegloticase 45 . By comparison, the hierarchical approach to evidence used by the ACP panel placed unbending emphasis on the randomized controlled phases of clinical trials.…”
Section: Interpreting Limits Of Past Ult Trialsmentioning
confidence: 99%
“…In this issue of the journal, Kiltz et al published the treat-to-target (T2T) recommendations for gout,1 based on a systematic literature review (SLR) using standard methodology based on Oxford Center for Evidence-based Medicine system and the AGREE criteria 2 3. The expert group developed nine T2T recommendations for gout management.…”
mentioning
confidence: 99%
“…Inherent to achieving target sUA was the recommendation that sUA should be measured regularly in patients with gout (moderate-level evidence), so that urate-lowering therapy (ULT) dose adjustment can be guided by the sUA level 1. An updated literature review of T2T strategies in gout identified is a lack of randomised trials that have tested the T2T strategy for gout versus other approaches.…”
mentioning
confidence: 99%
“…Следует обратить внимание, что предыдущие реко-мендации, касающиеся ведения пациентов с ранним РА [1], были фактически первыми, в которых именно дости-жение ремиссии рассматривалась как основная цель фар-макотерапии, и предвосхищали концепцию «Лечение до достижения цели -Treat to Target», сформулированную для РА [92], а затем других ревматических заболеваний, включая ПсА [93], спондилоартриты [94], подагру [95] и системную красную волчанку (СКВ) [96]. Доказано, что ремиссия ассоциируется с лучшими исходами, чем низкая активность болезни [97][98][99].…”
Section: рекомендация 8 (уровень доказательности Ib и Iv; сила рекомеunclassified